Dominican Republic HIV/AIDS Prevention and Control Project : Initial Results - Marquez, Patricio V.; Montalvo, Luis Emilio (World Bank, Washington, DC, 2012)
The Dominican Republic has 120,000 persons living with AIDS (PLWAs), 9 times the total number of reported cases. About 20,000 people have died from AIDS in the last decade. HIV/AIDS is the leading cause of death among women of reproductive age. Prevalence is highest (5 percent of adults) among low-income groups that include many Haitian immigrants living in rural communities and working in sugar cane plantations. Prevalence among female commercial sex workers is about 8 percent, reaching 12 percent in some cities. Tuberculosis (TB) is the largest opportunistic infection for PLWAs. PAHO estimates that over 100 persons per 100,000 are infected with TB, versus 2.6 per 100,000 in Barbados and 4.9 per 100,000 in Jamaica. The 5,320 reported cases in the Dominican Republic are among the highest in the Latin America and Caribbean region.